(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
“A throughout course of action for achieving objectives in Foreign relations as dedicated by the Ideology of National Interest”- Foreign PolicyThis definition of Foreign Policy in given by Prof. Mahendra Kumar, According to him, Foreign Policy includes (i) The Policy Makers (ii) Interest and objectives (iii) Principles of Foreign Policy (iv) Means of Foreign Policy – In the future section, we will mention all these paints in detail with references to our country foreign policy, therefore means deciding on certain goals and making efforts to regulate behavior of other adjusting their own activities i.e. National Internet to the International environment.“Now, we will study the Present Foreign Policy of India made an regulated by our Prime Minister Sh. Narender Modi.”